Frequency diverse array OFDM transmitter for secure wireless communication. Issue 17 (1st August 2015) - Ding, Y.; Zhang, J.; Fusco, V.
Abstract : In this reported work, the frequency diverse array concept is employed to construct an orthogonal frequency‐division multiplexing (OFDM) transmitter that has the capability of securing wireless communication in free space directly in the physical‐layer without the need for mathematical encryption. The characteristics of the proposed scheme in terms of its secrecy performance are validated via bit error rate simulation under both high and low signal to noise ratio scenarios using the IEEE 802.11 OFDM physical‐layer specification.